Object-oriented analysis and design with applications - Booch, Grady (Addison-Wesley, 2007)
Includes bibliographical references; There are: An introduction to the new UML 2.0, from the notation's most fundamental and advanced elements with an emphasis on key changes; New domains and contexts; A greatly enhanced focus on modeling--as eagerly requested by readers--with five chapters that each delve into one phase of the overall development lifecycle.;Fresh approaches to reasoning about complex systems; An examination of the conceptual foundation of the widely misunderstood fundamental elements of the object model, such as abstraction, encapsulation, modularity, and hierarchy; How to allocate the resources of a team of developers and mange the risks associated with developing complex software systems;An appendix on object-oriented programming languages.